2015
DOI: 10.1007/s00170-015-8139-2
|View full text |Cite
|
Sign up to set email alerts
|

A cost-effective method for rapid manufacturing sheet metal forming dies

Abstract: Time and expense are two main important issues that are needed to manufacture sheet metal forming dies in precision machinery industry. This study presents an alternative approach of producing sheet metal forming dies that is suitable for application in a new sheet metal component research and development phase. It was found that the sheet metal forming dies can be fabricated within 1 day. The advantages of the proposed method for fabricating sheet metal forming dies include low processing time and lower manuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…The tooling was tested using a hydraulic machine for forming of Al–Mg alloy sheets with a thickness of 0.6 mm. The tooling was proven to be effective experimentally and was found to be rigid enough to fulfill small batch production with good dimensional accuracies [ 22 ]. Schuh et al analyzed the suitability of 3D printed PLA tools for sheet metal.…”
Section: Classification Of Rapid Toolsmentioning
confidence: 99%
“…The tooling was tested using a hydraulic machine for forming of Al–Mg alloy sheets with a thickness of 0.6 mm. The tooling was proven to be effective experimentally and was found to be rigid enough to fulfill small batch production with good dimensional accuracies [ 22 ]. Schuh et al analyzed the suitability of 3D printed PLA tools for sheet metal.…”
Section: Classification Of Rapid Toolsmentioning
confidence: 99%
“…38 However, some disadvantages of these techniques include high investment in machinery, high operating costs and time-consuming processes. 39 In this context, Kuo and Li 40 proposed a rapid method for fabricating epoxy forming dies, as shown in Figure 4, to produce small batches of Al–Mg alloy sheet components. This study revealed that compared with the traditional method, the manufacturing cost of the mould was reduced by 87.2%.…”
Section: Recent Investigations Of Epoxy Toolingmentioning
confidence: 99%
“…In addition, the mould was made within 1 day.
Figure 4.Schematic diagram of manufacturing sheet metal forming dies: (a) Designing the master model; (b) Manufacture of the master model; (c) Removal of prototype support materials; (d) Surface treatment of prototype by sandblasting; (e) Manufacture of the silicone rubber mould; (f) Manufacture of the sheet metal forming dies. 40
…”
Section: Recent Investigations Of Epoxy Toolingmentioning
confidence: 99%
“…Examples of indirect RT methods are silicone rubber tooling, spray metal tooling and epoxy resin tooling. Epoxy resin punch and dies constructed through indirect rapid tooling technique reduce the cost involved in forming Al-Mg alloy sheets up to 87 per cent (Kuo and Li, 2016). Kuo (2018) fabricated wax filament through indirect tooling technique and manufactured wax conformal cooling channel using FDM.…”
Section: Applicationsmentioning
confidence: 99%